Analisis Strategi Pemasaran Influencer Marketing pada Online Shop Ziyadah ID di Depok - Surti Wardani; Arif Siaha Widodo (Al-Buhuts, 2023)
This study aims to analyse marketing strategies with influencer marketing at the ziyadah.id online shop in Depok. This type of research uses a qualitative descriptive narrative approach. Data collection using observation and semi-structured interviews. The data analysis technique uses SWOT analysis by making IFAS and EFAS matrices, weighting and formulating strategies: SO, WO, ST and WT. The results of the research on the IFAS matrix show that the strengths and weaknesses have a total score of 2.93; indicates that the ziyadah.id online shop is in a strong internal position. Next, the EFAS matrix shows the opportunity and threat factors with a total score of 3.70; indicates the company responds to existing opportunities in an extraordinary way and avoids threats in its industrial market. The Cartesian diagram shows that the online shop ziyadah.id l is in quadrant I, which is a favourable situation. The strategy that must be implemented is to support an aggressive growth policy (Growth Oriented Strategy/GOS) in order to maximize the strengths it has to seize opportunities and balance other competitors among online shops. In the SO strategy, a strength factor must be maintained to be able to take the opportunities that exist. The ST strategy coupling shows the company must maximize its strengths to overcome existing threats. The WO strategy shows that the company takes advantage of existing opportunities by minimizing the company's weaknesses. Whereas the WT strategy requires companies to minimize weaknesses and avoid threats.